2020
DOI: 10.3390/su12166392
|View full text |Cite
|
Sign up to set email alerts
|

Moderators of Change in Physical Activity Levels during Restrictions Due to COVID-19 Pandemic in Young Urban Adults

Abstract: This study aimed to investigate moderators of change in physical activity (PA) levels after 30 days (30-d) of restrictions due to the COVID-19 pandemic in young adults. This research is an extension of the CRO-PALS study and analyses for this study were performed on young adults (20–21 y.o., n = 91). Moderate-to-vigorous physical activity (MVPA), sport participation, student and socioeconomic status were assessed pre- and post-30-d restrictions. Differences in MVPA levels were examined using repeated-measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
53
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 23 publications
(42 reference statements)
8
53
4
Order By: Relevance
“…One thousand one hundred thirty-seven references were identified after search process in four databases, of which 10 (Ács et al, 2020 ; Barkley et al, 2020 ; Gallè et al, 2020 ; Gallo et al, 2020 ; Karuc et al, 2020 ; Maher et al, 2020 ; Romero-Blanco et al, 2020 ; Sañudo et al, 2020 ; Savage et al, 2020 ; Alarcón Meza and Hall-López, 2021 ) met the inclusion criteria. Figure 1 shows the flow chart of the selection process of the studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One thousand one hundred thirty-seven references were identified after search process in four databases, of which 10 (Ács et al, 2020 ; Barkley et al, 2020 ; Gallè et al, 2020 ; Gallo et al, 2020 ; Karuc et al, 2020 ; Maher et al, 2020 ; Romero-Blanco et al, 2020 ; Sañudo et al, 2020 ; Savage et al, 2020 ; Alarcón Meza and Hall-López, 2021 ) met the inclusion criteria. Figure 1 shows the flow chart of the selection process of the studies.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Sañudo et al ( 2020 ) showed an objective reduction in PA with 67.7% fewer steps per day during the lockdown. In the same line, five studies showed a reduction of light/mild PA (walking) between 32.5 and 365.5% compared to the period prior to confinement (Ács et al, 2020 ; Barkley et al, 2020 ; Gallè et al, 2020 ; Gallo et al, 2020 ; Sañudo et al, 2020 ), three studies found a decrease in moderate PA levels (from 14–59.7%) (Barkley et al, 2020 ; Gallè et al, 2020 ; Sañudo et al, 2020 ) and four studies in moderate-to-vigorous PA (MVPA) (from 3.9–56.6%) (Karuc et al, 2020 ; Maher et al, 2020 ; Sañudo et al, 2020 ; Savage et al, 2020 ). Finally, seven studies also revealed a reduction of high/vigorous PA between 2.9 and 52.8% compared to pre-lockdown (Ács et al, 2020 ; Barkley et al, 2020 ; Gallè et al, 2020 ; Gallo et al, 2020 ; Romero-Blanco et al, 2020 ; Sañudo et al, 2020 ; Alarcón Meza and Hall-López, 2021 ) and two studies showed a decrease of total PA (28.6 and 50%) (Ács et al, 2020 ; Gallè et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is a part of the CRO-PALS study, a longitudinal study conducted in a random sample of urban youth in Zagreb (Croatia). Details on the sampling and procedures of the study have been described elsewhere [43]. In brief, using stratified two-stage random sampling procedures (school level and class level), 54 classes in 14 secondary schools were selected to participate in the CRO-PALS study (schools were stratified by type: grammar schools/vocational schools/private schools).…”
Section: Participantsmentioning
confidence: 99%
“…This study was performed during the 2 nd wave of assessments, and all measurements were taken in 2015, during March, April, and May. Information about the procedures of the CRO-PALS longitudinal study have been documented in previous research [27]. In brief, using stratified two-stage random sampling procedures (school level and class level), 54 classes in 14 secondary schools were selected to participate in the CRO-PALS study (schools were stratified by type: grammar schools/vocational schools/private schools).…”
Section: Participantsmentioning
confidence: 99%